The Effect of Transformational Leadership, Job Training, and Work Safety on Employee Performance Through Quality of Work Life of Employees of PT Swadaya Graha - Mokhammad Fatikhul Ikhsan; Suhermin Suhermin (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine and analyze the effects of Transformational Leadership, Job Training, and Work Safety on employee performance, with Quality of Work Life as a mediating variable among employees of PT Swadaya Graha assigned to the PT Amman Mineral mining site in West Nusa Tenggara. This research adopts a quantitative approach with a causal and comparative design. The population of this study consists of all employees of PT Swadaya Graha, with a total sample of 185 respondents selected using a saturated sampling technique. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS version 3.0.The results indicate that Transformational Leadership, Job Training, and Work Safety have positive and significant effects on employee performance. These findings suggest that inspirational leadership, effective job training, and well-implemented work safety practices contribute to improved employee performance. However, Quality of Work Life does not significantly mediate the relationship between Transformational Leadership and employee performance. Meanwhile, Work Safety has a positive and significant effect on employee performance through Quality of Work Life, whereas Job Training does not show a significant indirect effect through Quality of Work Life. These results highlight the critical role of work safety in enhancing employees’ quality of work life and sustaining long-term performance.